Pengaruh Razia Lapangan, E-Samsat Dan Samsat Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Samsat Kabupaten Sukoharjo - Dhela Ekaningrum; Suprihati Suprihati; Rukmini Rukmini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research “looks at how the degree of motor vehicle taxpayer compliance in Sukoharjo Regency is affected by field raids, E-Samsat services, and Mobile Samsat. Quantitative research methodology is used, and primary data is gathered by distributing questionnaires to participants. A Likert scale served as the basis for the study instrument's design, which measured the variables under investigation. A total of 100 motor vehicle taxpayers who were registered at the Sukoharjo Regency Samsat Unit served as the study's participants. Out of this total, 50 respondents answered the survey online using a Google Form, while the other 50 respondents completed the questionnaire on paper. The accidental sampling approach was the sampling strategy utilized. The analysis's findings demonstrate that field raids and Mobile Samsat services significantly and favorably impact the degree of motor vehicle taxpayer compliance. In contrast, Sukoharjo RRegency's taxpayer compliance is significantly impacted negatively by the E-Samsat service.”